GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH DIVERSIFIKASI OPERASI DAN DIVERSIFIKASI GEOGRAFIS PADA MANAJEMEN LABA - Kusumayani, Ni Luh; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The study aims to reexamine the influence of operating diversification and geographical diversification on earnings management with good corporate governance (GCG) as moderating factor. The study was conducted on companies listed in the Indonesia Stock Exchange in 2010-2014 according to criteria purposive sampling. Data were analyzed by the use of multiple linear regression test and Moderated Regression Analysis. Modified Jones Model is used to detect earnings management. Operating diversification and geographical diversification is measured by the number of segments reported on the company's financial statements. GCG is measured by the score of companies in the Corporate Governance Perception Index. Based on research with 27 sample companies, it is known that operating diversification does not affect earnings management, whereas positive effect of geographical diversification. The study also found that GCG does not moderate the effect of operating diversification to earnings management, but weakens the influence to geographical diversification in earnings management.
Keywords: earnings management, operating diversification, geographical diversification, good corporate governance